Ujednolicanie polityki podatkowej w Unii Europejskiej - szansa czy zagrożenie dla rozwoju polskiej gospodarki? - Sosnowski, Michał (Harmonization of fiscal policies in the European Union - chance or threat for the Polish economy?, 2006)
The author presents the problem related to the proposals ofsome countries in the European Union, aimed at the harmonization of the definite regulations in the sphere of fiscal policy, and their influence on development ofthe Polish economy and level of competitiveness of Polish enterprises. In the author’s opinion the attempt of the harmonization relating only to the income tax rates would be a mistake and a threat for economic growth by the new members ofthe European Community. However it’s worthwhile to bring for the further discussion the issue concerning standardization of rules for determining the taxation base.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 160-169